2011
DOI: 10.4081/cp.2011.e83
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide-Induced Cardiac Arrest

Abstract: The authors report a case of cardiac arrest in a patient receiving intravenous (IV) metoclopramide and review the pertinent literature. A 62-year-old morbidly obese female admitted for a gastric sleeve procedure, developed cardiac arrest within one minute of receiving metoclopramide 10 mg via slow intravenous (IV) injection. Bradycardia at 4 beats/min immediately appeared, progressing rapidly to asystole. Chest compressions restored vital function. Electrocardiogram (ECG) revealed ST depression indicative of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…However, in our study, there was no difference between domperidone and metoclopramide in the odds of ventricular arrhythmia (aOR 1.06, 95%CI [0.91–1.23]). Our findings thus echo previous studies in which metoclopramide was associated with ventricular arrhythmia . As with domperidone, clinical attention to QT prolongation and pro‐arrhythmic events is warranted when metoclopramide is administered.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, in our study, there was no difference between domperidone and metoclopramide in the odds of ventricular arrhythmia (aOR 1.06, 95%CI [0.91–1.23]). Our findings thus echo previous studies in which metoclopramide was associated with ventricular arrhythmia . As with domperidone, clinical attention to QT prolongation and pro‐arrhythmic events is warranted when metoclopramide is administered.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings thus echo previous studies in which metoclopramide was associated with ventricular arrhythmia. [24][25][26][27] As with domperidone, clinical attention to QT prolongation and proarrhythmic events is warranted when metoclopramide is administered.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, after the one-week therapy, there were clinically related changes in the ECG of two patients of the metoclopramide group, particularly prolongation of QT intervals. In similarity to the findings of the current study, other studies and case reports have reported cardiotoxic effects caused by metoclopramide especially with higher doses and with long-term use [44,45].…”
Section: Safetysupporting
confidence: 92%
“…The European Committee also recommended to use metoclopramide with caution in patients with cardiac conduction disturbances, bradycardia and in those taking other drugs known to prolong the QT interval [10]. In fact, cases of metoclopramide-related cardiovascular adverse effects have been reported in the literature [11].…”
Section: Discussionmentioning
confidence: 99%